Design E-LKPD based Problem Based Learning for Creative Thinking Skills on Fluid Materials - Satria, Yogi (PILLAR OF PHYSICS EDUCATION, 2025)
The context of 21st century education, together with the independent curriculum, is to create new abilities and skills and develop students' potential. These skills and abilities are expected to equip students to overcome the challenges of 21st century education. The potential that is developed is the ability to think that is given to humans. One of the abilities expected in 21st century learning is creative thinking. The need for creative thinking skills can be seen in the teaching materials used, one of which is the E-LKPD. This is evident in the essay questions given to students, which are still considered insufficient. One effort that can be made to improve creative thinking skills is the development of interactive teaching materials such as (E-LKPD). This study aims to produce PBL-based E-LKPD to improve students' creative thinking skills in fluid material that is valid and practical. The type of research conducted is Research and Development (R&D) using the 4D model (Define, Design, Development, Disseminate). The analysis stage includes needs analysis, curriculum analysis, student analysis, and task analysis. In the design stage, E-LKPD is designed by adjusting it to the E-LKPD components. During the development stage, validity testing was conducted by experts, and practicality testing was conducted by teachers and students. Based on the research conducted, the initial analysis results indicate that the development of E-LKPD has significant potential, with a percentage of 87.5%. The validity testing results indicate that the developed E-LKPD is highly valid, with an average validity index score of 0.913, categorized as highly valid. The practicality test results by teachers yielded an average score of 96.58, categorized as highly practical. The practicality test results by students yielded an average score of 94.21. Based on the research conducted, it can be concluded that the E-LKPD based on problem-based learning for fluid dynamics material that has been developed is valid and practical.